High-Intensity Interval Training Is Equivalent to Moderate-Intensity Continuous Training for Short- and Medium-Term Outcomes of Glucose Control, Cardiometabolic Risk, and Microvascular Complication Markers in Men With Type 2 Diabetes - Wormgoor, Shohn G.; Dalleck, Lance C.; Zinn, Caryn; Borotkanics, Robert; Harris, Nigel K. (Frontiers in Endocrinology, 2018)
We sought to determine the efficacy of 12 weeks high-intensity interval training (HIIT), compared to moderate-intensity continuous training (MICT) on glucose control and macro- and microvascular complication markers in men living with type 2 diabetes (T2D). Both modalities were combined with resistance training (RT). Additionally, the study aimed to determine the medium-term durability of effects. After a 12-week, thrice weekly, training intervention incorporating either MICT+RT (n=11) or HIIT+RT (n=12), the study concluded with a 6-month follow-up analysis. The middle-aged study participants were obese, had moderate duration T2D and were taking multiple medications including insulin, statins and beta-blockers. Participants, randomised via the method of minimisation, performed MICT (progressing to 26-min at 55% maximum estimated workload [eWLmax]) or HIIT (progressing to two variations in which twelve 1-min bouts at 95% eWLmax interspersed with 1-min recovery bouts, alternated with eight 30-sec bouts at 120% eWLmax interspersed with 2:15 min recovery bouts) under supervision at an exercise physiology facility. To account for fixed and random effects within the study sample, mixed-effect models were used to determine the significance of change following the intervention and follow-up phases and to evaluate group*time interactions. Beyond improvements in aerobic capacity (P<0.001) for both groups, both training modalities elicited similar group*time interactions (P>0.05) while experiencing benefits for glycated haemoglobin (HbA1c; P=0.01), subcutaneous adiposity (P<0.001) and heart rate variability (P=0.02) during the 12-week intervention. Adiposity (P<0.001) and aerobic capacity (P<0.001) were significantly maintained in both groups at the 6-month follow-up. In addition, during the intervention, SPs in both MICT+RT and HIIT+RT experienced favourable reductions in their medication usage. The study reported the inter-individual variability of change within both groups, the exaggerated acute physiological responses (using exercise termination indicators) that occurred during the interventions as well as the incidence of precautionary respite afforded in such a study sample. To reduce hyperglycaemia, and prevent further deterioration of macro- and microvascular complication markers (in both the short- and medium-term), future strategies that integrate the adoption and maintenance of physical activity as a cornerstone in the treatment of T2M for men should (cognisant of appropriate supervision) include either structured MICT+RT, or HIIT+RT.